PENGUNAAN METODA LEARNING MANAGEMENT SYSTEM (LMS) SECARA DARING PADA MATERI KULIAH HIDROLOGI DI SIAK UNIVERSITAS MUHAMMADIYAH GUNA PENINGKATAN PEMAHAMAN DAN PRESTASI BELAJAR MAHASISWA PRODI TEKNIK SIPIL - Selpa Dewi; Ambiyar Ambiyar; Nizwardi Jalinus; Wakhinuddin Wakhinuddin (Jurnal Dedikasi Pendidikan, 2021)
Muhammadiyah University as an educational institution under the auspices of the Muhammadiyah union has a central role in creating the quality of students excel in the world of education. Among academics a structured system of education (teaching and learning process) becomes inseparable. The implementation of e-learning method seems to be a necessity in the massive 4.0 era of information technology. The purpose of this research is to know the standardization of the application of e-learning methods at muhammadiyah university in Sumatra through a media portal that is often called SIAK or (academic information system) for Hidology courses that will be found by civil engineering students in semester 3 and will be continued in hydraulics courses in semesters 4 and 5. The research method used in the form of meta-analysis method where the research was conducted using the results of previous research to produce conclusions with qualitative descriptive analysis. The result of this study is the media of e-learning implementation in accordance with scorm standardization, namely Schoology and e-learning portal. This indicates that Muhammadiyah University in Sumatra has been maximized in the application of standardization of e-learning concept in each course and accumulated in each material.